Natural infection of tropical forage legume species of Arachis and Stylosanthes by potyviruses related to peanut mottle virus - Morales, Francisco José; Castaño, M.; Velasco, Ana Cecilia; Arroyave, José A. (Scientific Societies, 1991)
The South American forage legume Arachis pintoi was found to be affected by foliar ring spot symptoms in surveys of various localities in the Cauca Valley of Colombia. A filamentous virus (approximately 750 nm) isolated from symptomatic A. pintoi plants induced the characteristic ring spot symptoms in manually inoculated virus-free A. pintoi plants. This virus also caused systemic infection of other legumes, such as common bean, cowpea, peanut, and soybean, in manual transmission tests. A similar virus was also found in these surveys causing mild chlorosis and leaf malformation of another neotropical forage legume, Stylosanthes sp., which is closely related to the genus Arachis. The Stylosanthes virus systemically infected Stylosanthes spp., common bean, cowpea, and peanut by manual inoculation but not soybean. Of the nonlegumes tested, only Nicotiana benthamiana was systemically infected by both viruses. The A. pintoi and Stylosanthes sp. viruses were serologically related to each other and to peanut mottle virus (PMoV), and both induced cytoplasmic inclusions similar to those reported for PMoV. Differences between the viruses isolated in this investigation and PMoV must be studied further before these tropical forage legume potyviruses can be considered strains of PMoV.